GP.4 Can Quantitative Susceptibility Mapping Help Diagnose and Predict Recovery of Concussion in Children?. (November 2021) - Sader, N; Gobbi, D; Goodyear, B; Frayne, R; Beauchamp, M; Craig, WR; Doan, Q; Zemek, R; Yeates, KO; Riva-Cambrin, J
Abstract : Background: Quantitative susceptibility mapping (QSM) is an MR sequence that has potential as a biomarker in concussion. We compared QSM in pediatric concussion patients versus a comparison group of children with orthopedic injuries (OI) and assessed QSM's performance relative to the current clinical benchmark (5P risk score) for predicting persistent postconcussion symptoms (PPCS). Methods: Children ( N =967) aged 8-16.99 years with either concussion or OI were prospectively recruited from 5 Canadian centers. Participants completed QSM at a post-acute assessment 2-33 days post-injury. QSM z-score metrics for 9 regions of interest (ROI) were derived from 371 children (concussion=255, OI=116). PPCS at 1-month post-injury was defined using reliable change methods. Results: The concussion and OI groups did not differ significantly in QSM across ROI. Increased frontal white matter (WM) susceptibility predicted reliable increases in parent-rated cognitive symptoms (p=0.001). Together, frontal WM susceptibility and the 5P risk score were better at predicting persistent cognitive symptoms than the 5P risk score alone (p=0.0021). AUC were 0.71(95%CI: 0.62-0.80) for frontal WM susceptibility, 0.67(95%CI: 0.56-0.78) for the 5P risk score, and 0.73(95%CI: 0.64-0.82) for both. Conclusions: This is the first study to demonstrate a potential imaging biomarker that predicts persistent symptoms in children with concussion compared to the current clinical benchmark.